Can we anti‐consume our way to sustainability? Finding answers at the intersection of cultural values. Issue 5 (28th December 2020) - Kuanr, Abhisek; Israel, Duraipandian; Pradhan, Debasis; Roy Chaudhuri, Himadri
Abstract: Anti‐consumption behaviours are frequently seen as an effective way for an individual to mitigate harm done to the natural world and foster sustainability. Despite explicit calls to investigate the drivers of anti‐consumption behaviours, the effect of cultural values on anti‐consumption remains under‐researched. Our research examines the influence of two antecedents, cultural values (individualism and collectivism), and self‐efficacy on anti‐consumption behaviours in an emerging country setting. Our results indicate that cultural values influence anti‐consumption behaviours. Consistent with our expectations, we found that collectivistic values positively influenced anti‐consumption behaviours. This relationship remained valid across anti‐consumption behaviours, such as voluntary simplicity and brand avoidance. Furthermore, beyond our initial expectation, this study demonstrated a positive indirect relationship between individualism and anti‐consumption, which is activated through the self‐efficacy pathway. These findings suggest that approaches for managing anti‐consumption behaviour do not work equally well in all cultures, and that managers may need to fine‐tune their international marketing strategies to ensure their effectiveness.